The Gender Stereotyping of Musical Instruments in the Western Tradition - Steblin, Rita (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1995)
The sexual stereotyping of musical instruments in Italian, German, and English society from the beginning of the Renaissance period to the end of the nineteenth century is the object of this essay. Through evidence gleaned from iconography and a variety of written documents, the author demonstrates how the gender association of musical instruments virtually eliminated female participation from important musical activities, ensuring the male domination of the art and preventing women from becoming prominent composers.